Tensile characterizations of oil palm empty fruit bunch (OPEFB) fibres reinforced composites in various epoxy/fibre fractions - Faizi, Mohd Khairul; Abu Bakar, Shahriman; Abdul Majid, Mohd Shukry; Mohd Tamrin, Shamsul Bahri; Israr, Haris Ahmad; Abdul Rahman, Anas; Ng, Yee Guan; Mohd Razlan, Zuradzman; Kamis, Norzarul Asri; Wan Ahmad, Wan Khairunizam (Biointerface Research in Applied Chemistry, 2021)
Oil palm empty fruit bunch (OPEFB) single fibers and reinforced composites were comprehensively characterized through tensile tests to assess their performance as potential reinforcing materials in polymer composites. The performances of OPEFB single fibers and reinforced composites with untreated and treated fibers conditions were compared. The fibers were variously treated with 3% sodium hydroxide, 2% silane, 3% sodium hydroxide mixed with 2% silane, and 3% sodium hydroxide prior to 2% silane for 2 hours soaking time. The highest toughness of the single fibers test was then selected to proceed with composites fabrication. The OPEFB composites were fabricated in 90:10, 80:20, 70:30, and 60:40 epoxy-fibre fractions. The result shows that the selected treated fiber composite exhibits better performance. The selected treated fiber composite increased the highest ultimate tensile strength by 145.3% for the 90:10 fraction. The highest Young’s Modulus was increased by about 166.7% for 70:30 fraction. Next, the highest toughness was increased by 389.5% for the 30:70 fraction. The treated fibers provided a better interlocking mechanism between the matrix and fibers in reinforced composites, thus improving their interfacial bonding.